Pulmonary Embolism Following Percutaneous Nephrolithotomy: A Rare Case Report - Maharjan, Bipin; Adhikari, Mahesh Bahadur; Khadga, Ajit; Gautam, Ravi Kiran; Mishra, Prashant; Basnet, Birodh; Yadav, Deepak Kumar (Nepal Mediciti Medical Journal, 2025)
Percutaneous nephrolithotomy (PCNL) is one of the most common treatment options for renal stones in Nepal. Common complications include perioperative bleeding, urine leak from a nephrocutaneous fistula, pelvicalyceal system injury, and pain; these are individually graded by various authors and contribute to significant variability in reported overall PCNL complication rates. We report the case of a previously healthy 53-year-old female who developed acute pulmonary embolism (PE) following left prone mini percutaneous nephrolithotomy. Computed tomography pulmonary angiography confirmed an acute thrombus in the right descending pulmonary artery. The patient underwent immediate thrombolysis, leading to an uneventful postoperative recovery. This case highlights the critical importance of early diagnosis and prompt, efficient management of pulmonary embolism after PCNL, and underscores the need for timely intervention to achieve favourable outcomes.